Knowledge of Cervical Cancer and Awareness of It’s Screening among Women of Childbearing Age in Ilishan-Remo Community, Ogun State (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
With an expected 14,943 new cases and 10,403 fatalities from cervical cancer in 2020 alone, Nigeria faces a serious health crisis. Cervical cancer screening knowledge and awareness among Nigerian women are usually low, according to studies; this low level of awareness is caused by a number of factors, including cultural beliefs, religious practices, and limited access to healthcare services.This study therefore was designed to investigate the knowledge of cervical cancer and awareness of cervical cancer screening among women of childbearing age in Ilishan-Remo community, Ogun state, Nigeria.      The study employed a descriptive cross-sectional study design, and convenience sampling technique was used to select 289 women of childbearing age in Ilishan-Remo Community. A pre-tested questionnaire adapted with reliability of score of 0.86. Level of knowledge of cervical cancer was assessed using a 20-point scale categorized into poor (14). Data were analyzed using descriptive and inferential statistics of Pearson product moment correlation coefficient set at a significance level of 0.05.According to the study, 41.9% of respondents had a strong understanding of cervical cancer, and 39% were aware that cervical cancer screening is on the low side. The study's findings showed that although there is good knowledge about cervical cancer, there is little awareness of its screening. There is a significant relationship between age of women and knowledge of cervical cancer among women of child bearing age in Ilishan-Remo, Ogun State. (r=0.676, p=0.00